Exploring the Role of a Putative Secondary Metabolite Biosynthesis Pathway in Mycobacterium abscessus Pathogenesis Using a Xenopus laevis Tadpole Model - Nicholas James Miller; Dionysia Dimitrakopoulou; Laurel A. Baglia; Martin S. Pavelka; Jacques Robert (Microorganisms, 2024)
Mycobacterium abscessus (Mab) is an emerging human pathogen that has a high rate of incidence in immunocompromised individuals. We have found a putative secondary metabolite pathway within Mab, which may be a key factor in its pathogenesis. This novel pathway is encoded in a gene cluster spanning MAB_0284c to 0305 and is related to Streptomyces pathways, producing the secondary metabolites streptonigrin and nybomycin. We constructed an in-frame deletion of the MAB_0295 (phzC) gene and tested it in our Xenopus laevis animal model. We have previously shown that X. laevis tadpoles, which have functional lungs and T cells, can serve as a reliable comparative model for persistent Mab infection and pathogenesis. Here, we report that tadpoles intraperitoneally infected with the ∆phzC mutant exhibit early decreased bacterial loads and significantly increased survival compared with those infected with WT Mab. ∆phzC mutant Mab also induced lower transcript levels of several pro-inflammatory cytokines (IL-1β, TNF-α, iNOS, IFN-γ) than those of WT Mab in the liver and lungs. In addition, there was impaired macrophage recruitment and decreased macrophage infection in tadpoles infected with the ∆phzC mutant, by tail wound inoculation, compared to those infected with the WT bacteria, as assayed by intravital confocal microscopy. These data underline the relevance and usefulness of X. laevis tadpoles as a novel comparative animal model to identify genetic determinants of Mab immunopathogenesis, suggesting a role for this novel and uncharacterized pathway in Mab pathogenesis and macrophage recruitment.